ln(6)+ln(x)=ln(6x)

Simple and best practice solution for ln(6)+ln(x)=ln(6x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for ln(6)+ln(x)=ln(6x) equation:


Simplifying
ln(6) + ln(x) = ln(6x)

Reorder the terms for easier multiplication:
6ln + ln(x) = ln(6x)

Multiply ln * x
6ln + lnx = ln(6x)

Remove parenthesis around (6x)
6ln + lnx = ln * 6x

Reorder the terms for easier multiplication:
6ln + lnx = 6ln * x

Multiply ln * x
6ln + lnx = 6lnx

Solving
6ln + lnx = 6lnx

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Add '-6lnx' to each side of the equation.
6ln + lnx + -6lnx = 6lnx + -6lnx

Combine like terms: lnx + -6lnx = -5lnx
6ln + -5lnx = 6lnx + -6lnx

Combine like terms: 6lnx + -6lnx = 0
6ln + -5lnx = 0

Factor out the Greatest Common Factor (GCF), 'ln'.
ln(6 + -5x) = 0

Subproblem 1

Set the factor 'ln' equal to zero and attempt to solve: Simplifying ln = 0 Solving ln = 0 Move all terms containing l to the left, all other terms to the right. Simplifying ln = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Subproblem 2

Set the factor '(6 + -5x)' equal to zero and attempt to solve: Simplifying 6 + -5x = 0 Solving 6 + -5x = 0 Move all terms containing l to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -5x = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -5x = 0 + -6 -5x = 0 + -6 Combine like terms: 0 + -6 = -6 -5x = -6 Add '5x' to each side of the equation. -5x + 5x = -6 + 5x Combine like terms: -5x + 5x = 0 0 = -6 + 5x Simplifying 0 = -6 + 5x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| 42a^2+a-30=0 | | 6a^2-28a+16= | | 28/5 | | 36=b(5)(6) | | (B/9)-.5=(5/18) | | (x)(-3)-4=-10 | | 81x+36x+20=0 | | (3x^-5/8y^-7)^-2 | | 0=20t-5(t^2)+25 | | 4x-3/8 | | 6x-2x+7=x-2+9 | | 5x+6=30+x | | 30xm+15xn-20ym-10yn= | | 25x^4-81y^2=0 | | 1/4x=x-33 | | 5-(-3)+6= | | f(x)=-4x^2+16x-5 | | x/(36x^2-9) | | x+2x+5x=32 | | x^2+14xy+24y=0 | | 5+4ln(x)=7 | | x/36x^2-9 | | m^2+22m-4=0 | | y^4-6y^3+12y^2-10y+3= | | a=-1e+-1s+-1y | | w^2-13w+42.25=0 | | 1/4x^4-9/25=0 | | ydx=x(lnx-lny)dy | | 5x=(3x-3)(m+4) | | 0.90n=n+15 | | -17+8x=14 | | 0.75p=18 |

Equations solver categories